An Analysis of Media Agenda-Setting During the Covid-19 Pandemic in Indonesia: Implications for Disaster Preparedness, Response, And Policy - ., Rudianto (Journal of Cultural Analysis and Social Change, 2025)
Mainstream media shape public understanding and policy attention during health crises. In Indonesia’s COVID-19 pandemic, how national online media prioritized disaster-management phases remains underexamined. To analyze agenda-setting patterns in Indonesian national online media and assess whether coverage emphasized mitigation/preparedness versus response/recovery, alongside accountability focus, framing, tone, and policy/health orientation. A quantitative content analysis of 16 news articles (2020–2021) from Kompas.com, Detik.com, Tempo.co, and CNNIndonesia.com coded for phase (mitigation, preparedness, response, recovery), accountability actors, framing (thematic/episodic), tone (positive/neutral/negative), and presence of health context and policy focus. Coverage concentrated on response (68.7%) and recovery (18.7%), with minimal attention to mitigation and preparedness (each 6.3%). Accountability was centralized on the national government (75%). Framing was entirely thematic (100%), and tone was predominantly neutral (62.5%). Most articles incorporated health context (87.5%) and a policy focus (93.7%). Indonesian online media displayed a reactive, state-centric agenda during COVID-19, privileging response/recovery over prevention-oriented phases. Strengthening media attention to mitigation and preparedness—and broadening accountability beyond the central government—could better support public risk education and resilience for future health emergencies.